Imidazole to NHC rearrangements at molybdenum centers: an experimental and theoretical study - Brill, Marcel; Díaz, Jesús; Huertos, Miguel A.; López, Ramón; Pérez, Julio; Riera, Lucía (Chemistry - a European journal, 2011)
Both manganese and rhenium complexes of the type [M(bipy)(CO)3(N-RIm)]+ (bipy=2,2′-bipyridine) undergo deprotonation of the central CH group of the N-alkylimidazole (N-RIm) ligand when treated with a strong base. However, the outcome of the reaction is very different for either metal. For Mn, the addition of the equimolar amount of an acid to the product of the deprotonation affords an N-heterocyclic carbene (NHC) complex, whereas for Re, once the deprotonation of the central imidazole CH group has occurred, the bipy ligand undergoes a nucleophilic attack on an ortho carbon, affording the CC coupling product. The extension of these studies to pseudo-octahedral [Mo(η3-allyl)(bipy)(CO)2(N-RIm)]+ complexes has allowed us to isolate cationic NHC complexes (MnI-type behavior), as well as their neutral imidazol-2-yl precursors. Theoretical studies of the reaction mechanisms using DFT computations were carried out on the deprotonation of [Mn(bipy)(CO)3(N-PhIm)]+, [Re(bipy)(CO)3(N-MesIm)]+, and [Mo(η3-C4H7)(bipy)(CO)2(N-MesIm)]+ complexes (Mes=mesityl) at the B3LYP/6-31G(d) (LANL2DZ for Mn, Re, and Mo) level of theory. Our results explain why different products have been found experimentally for Mn, Mo, and Re complexes. For Re, the process leading to a CC coupling product is clearly more favored than those forming an imidazol-2-yl product. In contrast, for Mn and Mo complexes, the lower stabilizing interaction between the central imidazole and ortho bipy C atoms, along with the higher lability of the ligands, make the formation of an NHC-type product kinetically more accessible, in good agreement with experimental findings.
Gesehen am 23.06.2022